Seroprevalence and genotypes of Toxoplasma gondii isolated from pigs intended for human consumption in Liaoning province, northeastern China. Issue 1 (December 2016) - Wang, Dawei; Liu, Yan; Jiang, Tiantian; Zhang, Guoxin; Yuan, Gaoming; He, Jianbin; Su, Chunlei; Yang, Na
Abstract Background Genetic information forToxoplasma gondii isolates from pigs in eastern, south, and southwestern regions of China has been reported previously. However, there are no data from pigs in the northeastern area of the country. To better understand the epidemiology ofT. gondii, we determined the seroprevalence and genotypes ofT. gondii from pigs slaughtered for human consumption in Liaoning province, northeastern China. Findings Out of 2063 pigs examined, 233 (11.26 %) were seropositive forT. gondii by the modified agglutination test (MAT), and viable parasites were isolated by bioassay in mice from 23 (9.87 %) of the 233 seropositive pigs. Fifteen out of 23 isolates were genotyped using 10 PCR-restriction fragment length polymorphism (RFLP) genetic markers including SAG1, SAG2, SAG3, BTUB, GRA6, c22-8, c29-2, L358, PK1 and Apico. One isolate was identified as ToxoDB genotype #3 (type II-variant), and one was genotype #1 or #3. The other 13 isolates were ToxoDB #9 (type Chinese 1). Conclusions To our knowledge, this is the first report ofT. gondii isolation and genotyping from pigs in northeastern China. This study indicates that pigs are a potential source for transmission ofT. gondii to humans, therefore poses a potential public health concern. The genotyping results revealed the presence of genotype Chinese 1 in northeastern China, enriching the scope ofT. gondii genotypes distribution in eastern Asia.